Cobalt-based hexagonal nanosheet with electrocatalytic activity, preparation and application thereof

Cobalt-based hexagonal nanosheets were prepared by melamine thermal reflux method and loaded with Ru single atoms, which solved the problem of coupling use of two-dimensional porous structure catalytic materials and single atom catalysts, and achieved high-efficiency electrocatalytic activity and low-energy consumption electrochemical performance.

CN116253366BActive Publication Date: 2025-02-07SHENYANG PHARMA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211512169.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-02-07
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the coupled use of two-dimensional porous structure catalytic materials and single-atom catalysts, resulting in inefficiency and high cost in electrochemical applications.

Method used

Cobalt-based hexagonal nanosheets with adjustable structure were prepared by melamine thermal reflux method, and the Ru single atoms were loaded and reduced during the synthesis process to form CoO hexagonal porous nanosheets with loaded Ru single atoms.

Benefits of technology

The kinetic rate during the oxygen evolution reaction is significantly improved, the electrochemical impedance and overpotential are reduced, the electrochemically active surface is increased, and the specific surface area of ​​the catalyst is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116253366B_ABST
    Figure CN116253366B_ABST
Patent Text Reader

Abstract

The present invention provides a cobalt-based hexagonal nanosheet with high-efficiency electrocatalytic activity. The first aspect of the present invention relates to a cobalt-based hexagonal nanosheet with high-efficiency electrocatalytic activity. The nanosheet is a cobalt oxide with a hexagonal structure, a thickness of 1nm to 2nm, a lateral dimension of 100 to 2000nm, and micropores in the nanosheet, and the average diameter of the micropores is 0.6 to 2nm. In the present invention, it is proposed to use melamine thermal induction to make cobalt hydroxide form a hexagonal two-dimensional structure, and melamine only acts as an inducer and does not participate in the reaction, and can be recycled, which significantly reduces the technical cost of the two-dimensional structure control method. The catalyst of the present invention, which has been structurally controlled and metal-loaded, has a very high specific surface area, a low electrochemical impedance, a low overpotential and a large electrochemical active surface, which significantly improves the kinetic rate in the oxygen evolution reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry and relates to a cobalt-based hexagonal nanosheet with high-efficiency electrocatalytic activity, and the preparation and application thereof. Background Art

[0002] Oxygen evolution reaction (OER) is an important half-reaction process of water decomposition to produce pure hydrogen. However, each oxygen molecule produced is accompanied by the transfer of four electrons (4OH – →2H2O+O2+4e – , E = 1.23V), which leads to slow reaction kinetics. In addition, due to the existence of overpotential of electrode materials, the actual voltage in oxygen evolution reaction is generally higher than 1.23V. Therefore, the development of catalysts with low overpotential and excellent electrochemical performance is the key to breaking the bottleneck of kinetic sluggishness and reducing energy consumption. Theoretically, nano one-dimensional structures should show the largest specific surface area, but they are prone to severe clustering characteristics. Therefore, in many cases, two-dimensional porous structures are the preferred way to regulate catalyst structure. Generally, some high-temperature resistant materials have been used as hard templates for preparing porous materials to obtain surface defects. However, the sacrificial template method has great disadvantages: it is difficult to form micropores and it is difficult to remove the template. Therefore, it is necessary to develop an effective strategy to make the material grow microporous structure itself during the preparation process. Because the two-dimensional topological phase material has atomic-level thickness and a large lateral extension surface, it can show excellent edge electrocatalytic activity and expose a larger active surface, providing more favorable conditions for electron migration. Its interesting physicochemical properties have aroused researchers' strong interest in two-dimensional nanomaterials with regular morphology and high aspect ratio.

[0003] CN 113957458 discloses a g-C3N4 / two-dimensional porphyrin MOF composite material formed by combining g-C3N4 nanomaterials with two-dimensional porphyrin MOF materials. The materials involved show an appropriate band gap width, which is conducive to the transition transfer of electrons and can electrocatalytically reduce CO2 to clean fuels CO and H2. CN 106486681 describes a two-dimensional material-supported composite catalyst. The special functional groups on the surface of the two-dimensional carrier and the interaction between them and the supported metal can make the catalyst show resistance to sulfur dioxide poisoning. The two-dimensional nickel-carbon nanosheet catalyst described in CN 110479271 is a two-dimensional Ni-MOF calcined and carbonized in a nitrogen atmosphere, and exhibits stable and efficient catalytic hydrogen evolution performance in an alkaline environment. CN 112853396 discloses a two-dimensional ultra-thin metal organic framework nanosheet electrocatalyst. The electrocatalyst involved adopts a method combining electrochemical exfoliation and liquid-phase ultrasonic-assisted exfoliation to form an ultra-thin two-dimensional structure, which shows high catalytic activity and stability in oxygen evolution reaction. CN 113130923 discloses a two-dimensional porous carbon composite material, which uses graphene or MXene as a matrix to form porous carbon, and widely distributes metal or intermetallic compound nanoparticles in the pores. This form is conducive to preventing the metal catalyst from agglomerating or falling off the carrier. The two-dimensional porous carbon-supported catalyst involved is used as an electrode catalyst for a fuel cell, and exhibits very high electrocatalytic activity and stability.

[0004] In addition, single-atom catalysts have attracted widespread attention due to their many advantages in electrochemical properties. Single-atom catalysts exhibit extremely high atomic efficiency and can change the surface electronic structure of the original catalyst to form new electron transfer and storage sites. CN 110961134 discloses a series of single-atom catalyst synthesis methods, which involve catalysts using Fe, Co, Ni, Pt, Au or Pd as metal sources and polystyrene nanospheres as sacrificial templates to form corresponding single-atom catalytic materials under acidic conditions, showing excellent catalytic performance.

[0005] The high efficiency of electrochemical catalytic activity of catalytic materials with two-dimensional porous structures and single-atom catalysts has been widely recognized in the field of electrochemical technology. However, the means of regulating the two-dimensional porous structure of ordinary materials is still a major technical challenge. Technical means such as chemical or physical exfoliation, two-dimensional MOFs as precursors, graphene as carriers or sacrificial template methods all have problems such as cost or complex processes. In addition, due to the harsh conditions for the formation of single-atom catalysts, the coupled use of two-dimensional porous structure catalytic materials and single-atom catalytic materials is still difficult to promote. Summary of the invention

[0006] Based on the above background, the present invention prepares a cobalt-based hexagonal nanosheet with a two-dimensional porous structure, and relates to a method for synchronously loading and reducing Ru single atoms during the synthesis process. In the present invention, a series of cobalt-based hexagonal nanosheets with adjustable structures formed by the melamine thermal reflux method are proposed. Since melamine is stable in nature, it only acts as an inducer and does not participate in chemical reactions during the preparation process. Therefore, the control means involved in the present invention can be used for solid-liquid separation after the catalyst is synthesized, and the inducer solution can continue to be used, which significantly reduces the technical cost of the two-dimensional structure control means. When cobalt hydroxide is formed in the melamine solution, the strong intermolecular interaction force causes the cobalt hydroxide crystals to grow in a directional manner. And the lateral extension scale of the nanosheet can be adjusted by different melamine concentrations, so that the structure of the metal semiconductor has the same controllability as a metal organic framework. In Co 2+ And Ru 3+ Adding melamine to the coexisting solution can produce layered double hydroxides, embedding Ru(OH)3 into Co(OH)2 hexagonal nanosheets, and then calcining under inert gas protection to simultaneously obtain a two-dimensional porous catalyst of cobalt oxide loaded with single-atom ruthenium. It is worth noting that during the calcination process, the layered double hydroxides are dehydrated, and after the water molecules escape, micropores with a diameter of 0.6 to 2 nm are formed in situ on the nanosheets. The surface area of ​​the two-dimensional porous catalyst is more than ten times larger than that of one-dimensional nanoparticles. The nanosheets prepared by the structural regulation strategy involved in the present invention are only 1nm to 2nm thick, while the lateral scale can reach 100 to 2000nm, with a high specific surface area, and at the same time exhibit excellent catalytic activity in electrocatalytic applications.

[0007] The first aspect of the present invention relates to a cobalt-based hexagonal nanosheet with high electrocatalytic activity, wherein the nanosheet is a hexagonal cobalt oxide with a thickness of 1nm to 2nm and a lateral dimension of 100 to 2000nm, and the nanosheet has micropores with an average diameter of 0.6 to 10nm. The surface area of ​​the two-dimensional porous catalyst of the present invention is more than ten times larger than that of one-dimensional nanoparticles, and exhibits excellent catalytic activity in electrocatalytic applications.

[0008] In a preferred embodiment of the present invention, the cobalt-based hexagonal nanosheets are loaded with single Ru atoms. By loading single Ru atoms on the cobalt-based hexagonal nanosheets, the catalyst has a more active charge storage and transfer capability. At the same current density, the CoO hexagonal porous nanosheets loaded with single Ru atoms exhibit a lower overpotential; and its Tafel slope is only about half of that of ordinary CoO, proving that a small amount of single Ru atoms dispersed and two-dimensional porous structure regulation can significantly improve the kinetic rate in the oxygen evolution reaction.

[0009] In a preferred embodiment of the present invention, the loading amount of the Ru single atom is 0-5 wt %, preferably 1-1.5 wt %. Within this preferred range, it is most beneficial to improve the catalytic activity.

[0010] The second aspect of the present invention relates to a method for preparing the above-mentioned cobalt-based hexagonal nanosheets, which is characterized by comprising the following steps:

[0011] Cobalt nitrate is added to a solution containing melamine, and optionally, an aqueous solution of a ruthenium salt is also added;

[0012] Add ammonia water and heat under reflux to react;

[0013] Centrifugation is used to separate solid and liquid, and the solid is washed with water and dried;

[0014] Cobalt-based hexagonal nanosheets are obtained by calcination under nitrogen or inert atmosphere.

[0015] The present invention regulates the structure of cobalt-based hexagonal nanosheets and the metal-loaded catalyst through the preparation method, has a very high specific surface area, a low electrochemical impedance, a low overpotential and a large electrochemical active surface, and significantly improves the kinetic rate in the oxygen evolution reaction process.

[0016] In a preferred embodiment of the present invention, the melamine solution obtained by the solid-liquid separation is recycled.

[0017] In a preferred embodiment of the present invention, the amount of cobalt nitrate added is 1-100 g / L; the concentration of melamine is 5-40 g / L.

[0018] In a preferred embodiment of the present invention, the dosage of the aqueous ammonia is 5-100 mL / L, the temperature during heating and reflux is 30-80° C., and the heating time is 0.5-2 h.

[0019] In a preferred embodiment of the present invention, the reaction system after the reaction is immediately subjected to solid-liquid separation in a centrifuge to prevent melamine from crystallizing due to solution cooling.

[0020] In a preferred embodiment of the present invention, the heating rate during the calcination process is 1.0-3.0°C / min; the calcination temperature is 325-525°C; and the calcination time is 1-2h.

[0021] In a preferred embodiment of the present invention, the ruthenium salt aqueous solution is prepared by the following steps: anhydrous ruthenium chloride is completely dissolved in

[0022] Preferably, the ruthenium salt concentration in the ruthenium salt aqueous solution is 0.1-1.0 wt %.

[0023] In a preferred embodiment of the present invention, the dosage of the ruthenium salt solution is 0.1-10 mL / L. Preferably, the mass ratio of the four raw materials of ruthenium salt, cobalt salt, melamine and ammonia water in each 1 L of the reaction system is 0-0.1:1.0-100.0:1.0-40.0:5.0-100.0.

[0024] The third aspect of the present invention relates to the application of the above-mentioned cobalt-based hexagonal nanosheets, wherein the cobalt-based hexagonal nanosheets are used to electrolyze water to generate hydrogen. The present invention has the following beneficial effects:

[0025] The catalyst of the present invention, which has undergone structural regulation and metal loading, has a very high specific surface area, a low electrochemical impedance, a low overpotential and a large electrochemically active surface, which significantly improves the kinetic rate in the oxygen evolution reaction process. The ultra-thin cobalt-based hexagonal nanosheets synthesized by melamine-induced directional growth have an ultra-high aspect ratio and show excellent electrochemical performance. The hydrothermal conditions can anchor ruthenium hydroxide on the cobalt hydroxide nanosheets. Under high temperature conditions, water molecules escape, allowing the material to self-grow a microporous structure. At the same time, Ru 3+ Restored to Ru 0 The valence state can form a hexagonal porous nanosheet of CoO loaded with Ru single atoms. With the difference of the inducer and its concentration, the catalyst can form different structures, which makes the structure of the metal semiconductor have the general controllability of the metal organic framework. The specific surface area of ​​the hexagonal porous nanosheet of CoO loaded with Ru single atoms (540.049 m 2 / g) shows a specific surface area several dozen times that of ordinary CoO materials (47.883 m 2 / g). At the same current density, the CoO hexagonal porous nanosheets loaded with Ru single atoms exhibited a lower overpotential; and its Tafel slope was only about half of that of ordinary CoO, proving that a small amount of single-atom Ru dispersion and two-dimensional porous structure regulation can significantly improve the kinetic rate in the oxygen evolution reaction. The present invention provides a method for controlling the directional growth of metal semiconductors and in-situ synchronous synthesis of single-atom Ru, which is of great significance for improving the inherent defects of traditional metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The electron microscope images of the synthetic materials under different melamine concentration conditions of the present invention are shown;

[0027] Figure 2 The spherical aberration transmission electron microscope image and lattice spacing image of the Ru single atom described in the present invention are shown;

[0028] Figure 3 The comparison of the specific surface area of ​​the catalyst of the present invention and that of ordinary CoO is shown in FIG.

[0029] Figure 4The width and thickness of the material after the two-dimensional structure is regulated according to the present invention are shown;

[0030] Figure 5 The electrochemical impedance spectra of the catalysts described in Examples 1-4 (catalysts 1-4, respectively) are shown;

[0031] Figure 6 The overpotentials of the catalysts described in Examples 1-4 (catalysts 1-4, respectively) are shown;

[0032] Figure 7 The electron microscope image of the catalyst described in Example 1 is shown;

[0033] Figure 8 The electron microscope image of the catalyst described in Example 1 is shown;

[0034] Fig. 9 The electron microscope image of the catalyst described in Example 1 is shown;

[0035] Fig.10 An electron microscope image of the catalyst described in Example 1 is shown. DETAILED DESCRIPTION

[0036] The following are some exemplary implementations, which describe the materials and application environments described in the present invention in detail so that technicians can understand them more clearly. However, the following examples and descriptions are not limiting conditions of the present invention. Under the technical background described in the present invention, different environmental scenarios, different improvement schemes or other equivalent replacement implementations can be carried out, which all belong to the scope described in the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0037] Example 1

[0038] Preparation method of catalyst 1:

[0039] 20 mg of anhydrous ruthenium chloride was dissolved in 1 mL of deionized water and ultrasonically dispersed at 500 W and 40 kHz for 15 minutes. Then the above 1 mL of ruthenium trichloride solution and 3 g of cobalt nitrate hexahydrate were added to 50 mL of a 10 g / L melamine solution. After that, 8 mL of 25% ammonia water was added, and the mixture was heated at reflux at 80 ° C for 1 hour. The product was immediately centrifuged in a centrifuge at a speed of 4000 r / min, and then washed and dried with water. Finally, the dried product was calcined at 525 ° C for 2 h under a nitrogen atmosphere to obtain CoO hexagonal porous nanosheets loaded with Ru single atoms, in which the Ru mass fraction was 1.25 wt%, expressed as Ru 1.25wt% After the specific surface area test, its specific surface area is 540.049m 2 / g.

[0040] Electrochemical performance test:

[0041] 3 mg of catalyst powder was dispersed in 1 mL of deionized water / ethanol solution with a volume ratio of 1:1, and then mixed with 10 μL of 10% Nafion solution. After ultrasonic dispersion, 5 μL of the mixed liquid was dropped on a circular glassy carbon electrode with a diameter of 5 mm and dried at 100 °C. Electrocatalytic measurements were performed on a CHI 660e electrochemical workstation using a rotating disk electrode. The coiled platinum wire was used as the counter electrode and the Hg / HgO electrode was used as the reference electrode. The electrolyte was a 1 M KOH aqueous solution. During the measurement, the working electrode was kept rotating at a rate of 1600 rpm. Electrochemical performance data such as linear sweep voltammograms, electrochemical impedance spectra, and cyclic voltammograms were obtained.

[0042] Test results:

[0043] The electrochemical performance test results are as follows:

[0044] Table 1: Electrochemical performance parameters of catalyst 1 under the environment described in Example 1

[0045]

[0046] The results show that: Load Ru 1.25wt% The overpotential of the single-atom CoO hexagonal porous nanosheet is only 308 mV, which is 63 mV lower than the overpotential of 371 Mv of the tested ordinary CoO; its Tafel slope is 58.89 mV dec. -1 , compared to the Tafel slope of the tested ordinary CoO of 113.82mV dec -1 , which is reduced by about 48.3%; its charge transfer impedance is 11.6Ω, which is about 68.3% lower than the charge transfer impedance of 36.6Ω of the tested ordinary CoO; its double layer capacitance reaches 74.1mF cm –2 , compared to the double-layer capacitance of the tested ordinary CoO of 23.6mF cm –2 , which increased by about 3.1 times. This proves that a small amount of single-atom Ru dispersion and two-dimensional porous structure regulation can significantly improve the kinetic rate of oxygen evolution reaction.

[0047] Example 2

[0048] Preparation method of catalyst 2:

[0049] The dosage of anhydrous ruthenium trichloride is 0. The remaining steps are the same as in Example 1 to obtain CoO hexagonal porous nanosheets, in which the mass fraction of Ru is 0wt%. After the specific surface area test, the specific surface area is 445.147m 2 / g.

[0050] Electrochemical performance test:

[0051] The testing method is the same as that in Example 1.

[0052] Test results:

[0053] The electrochemical performance test results are as follows:

[0054] Table 2: Electrochemical performance parameters of catalyst 2 under the environment described in Example 2

[0055]

[0056] The results show that the overpotential of the CoO hexagonal porous nanosheets with a two-dimensional porous structure is 348 mV, which is 23 mV lower than the overpotential of 371 Mv of the tested ordinary CoO; its Tafel slope is 74.06 mV dec -1 , compared to the Tafel slope of the tested ordinary CoO of 113.82mV dec -1 , which is reduced by about 34.9%; its charge transfer impedance is 23.7Ω, which is about 35.2% lower than the charge transfer impedance of 36.6Ω of the tested ordinary CoO; its double layer capacitance reaches 59.9mFcm –2 , compared to the double-layer capacitance of the tested ordinary CoO of 23.6mF cm –2 , which increased by about 2.5 times. This proves that the regulation of two-dimensional porous structure can significantly improve the kinetic rate of oxygen evolution reaction.

[0057] Example 3

[0058] Preparation method of catalyst 3:

[0059] 80 mg of anhydrous ruthenium chloride was dissolved in 1 mL of deionized water, and the remaining steps were the same as in Example 1 to obtain CoO hexagonal porous nanosheets loaded with Ru single atoms, wherein the mass fraction of Ru was 5 wt%, expressed as Ru 5wt% After the specific surface area test, its specific surface area is 115.286m 2 / g.

[0060] Electrochemical performance test:

[0061] The testing method is the same as that in Example 1.

[0062] Test results:

[0063] The electrochemical performance test results are as follows:

[0064] Table 3: Electrochemical performance parameters of catalyst 3 under the environment described in Example 3

[0065]

[0066] The results show that the overpotential of CoO hexagonal porous nanosheets loaded with a large amount of Ru single atoms is only 336mV, which is 35mV lower than the overpotential of 371Mv of the tested ordinary CoO; its Tafel slope is 94.82mV dec -1 , compared to the Tafel slope of the tested ordinary CoO of 113.82mV dec -1 , which is reduced by about 16.7%; its charge transfer impedance is 25.3Ω, which is about 30.9% lower than the charge transfer impedance of 36.6Ω of the tested ordinary CoO; its double layer capacitance reaches 36.0mF cm –2 , compared to the double-layer capacitance of the tested ordinary CoO of 23.6mF cm –2 , increased by about 1.5 times. This proves that compared with ordinary CoO materials, a large amount of single-atom Ru dispersion and two-dimensional porous structure regulation can improve the kinetic rate in the oxygen evolution reaction. However, compared with Example 1, it was found that a large amount of single-atom Ru loading would cause changes in the electrochemical properties and a significant decrease in the surface area of ​​the material, thereby causing a significant decrease in the double-layer capacitance, which may reduce the electrochemical catalytic efficiency.

[0067] Example 4

[0068] Preparation method of catalyst 4:

[0069] 3 g of cobalt nitrate hexahydrate was added to 50 mL of a 20 g / L melamine solution. After that, 8 mL of 25% ammonia water was added, and the mixture was heated at 80 ° C for 2 h under reflux. The product was immediately centrifuged at 4000 r / min in a centrifuge, and then washed and dried with water. Hexagonal cobalt hydroxide nanosheets with a two-dimensional structure were obtained. The difference from Examples 1, 2, and 3 is that no calcination was performed, and the amount of ruthenium salt added was 0. After the specific surface area test, its specific surface area is 180.401 m 2 / g.

[0070] Electrochemical performance test:

[0071] The testing method is the same as that in Example 1.

[0072] Test results:

[0073] The electrochemical performance test results are as follows:

[0074] Table 4: Electrochemical performance parameters of catalyst 4 under the environment described in Example 4

[0075]

[0076] The results show that the overpotential of the two-dimensional cobalt hydroxide hexagonal nanosheets is 342 mV, which is 29 mV lower than the overpotential of 371 Mv of the tested ordinary CoO; its Tafel slope is 89.48 mV dec. -1 , compared to the Tafel slope of the tested ordinary CoO of 113.82mV dec -1 , which is reduced by about 21.4%; its charge transfer impedance is 27.8Ω, which is about 24.0% lower than the charge transfer impedance of 36.6Ω of the tested ordinary CoO; its double layer capacitance reaches 34.7mF cm –2 , compared to the double-layer capacitance of the tested ordinary CoO of 23.6mF cm –2 , which increased by about 1.5 times. This proves that two-dimensional cobalt hydroxide also exhibits high electrocatalytic performance, and two-dimensional materials can show unique advantages in catalysis.

[0077] The above descriptions are only some embodiments of the present invention, but the protection scope of the present invention is not limited to the above cases. Formula improvements or equivalent replacements under the technical background should all fall within the scope of the present invention.

Claims

1. A cobalt-based hexagonal nanosheet with high electrocatalytic activity, characterized in that: The nanosheet is a hexagonal cobalt oxide with a thickness of 1 nm to 2 nm and a lateral dimension of 100 to 2000 nm. The nanosheet has micropores with an average diameter of 0.6 to 10 nm. The preparation method of the cobalt-based hexagonal nanosheet comprises the following steps: Cobalt nitrate is added to a solution containing melamine; Add ammonia water and heat under reflux to react; Centrifugation is used to separate solid and liquid, and the solid is washed with water and dried; Cobalt-based hexagonal nanosheets are obtained by calcination under nitrogen or inert atmosphere.

2. The cobalt-based hexagonal nanosheet according to claim 1, characterized in that: The cobalt-based hexagonal nanosheet is loaded with Ru single atoms, and the preparation method of the cobalt-based hexagonal nanosheet comprises the following steps: Cobalt nitrate is added to a solution containing melamine, and an aqueous solution of a ruthenium salt is also added; Add ammonia water and heat under reflux to react; Centrifugation is used to separate solid and liquid, and the solid is washed with water and dried; Cobalt-based hexagonal nanosheets are obtained by calcination under nitrogen or inert atmosphere.

3. The cobalt-based hexagonal nanosheet according to claim 2, wherein the loading amount of the Ru single atom is 0-5wt%.

4. The method for preparing the cobalt-based hexagonal nanosheets according to claim 1, characterized in that: The steps include: Cobalt nitrate is added to a solution containing melamine; Add ammonia water and heat under reflux to react; Centrifugation is used to separate solid and liquid, and the solid is washed with water and dried; Cobalt-based hexagonal nanosheets are obtained by calcination under nitrogen or inert atmosphere.

5. The method for preparing the cobalt-based hexagonal nanosheets according to claim 2, characterized in that: The steps include: Cobalt nitrate is added to a solution containing melamine, and an aqueous solution of a ruthenium salt is also added; Add ammonia water and heat under reflux to react; Centrifugation is used to separate solid and liquid, and the solid is washed with water and dried; Cobalt-based hexagonal nanosheets are obtained by calcination under nitrogen or inert atmosphere.

6. The preparation method according to claim 4 or claim 5, characterized in that: The melamine solution obtained by the solid-liquid separation is recycled.

7. The preparation method according to claim 4, wherein the amount of cobalt nitrate added is 1-100 g / L; and the concentration of melamine is 5-40 g / L.

8. The preparation method according to claim 4 or claim 5, characterized in that: The reaction system after the reaction is immediately subjected to solid-liquid separation in a centrifuge to prevent melamine from crystallizing due to solution cooling.

9. The preparation method according to claim 4 or claim 5, characterized in that: The heating rate during the calcination process is 1.0-3.0°C / min; the calcination temperature is 325-525°C; and the calcination time is 1-2h.

10. The preparation method according to claim 4 or claim 5, characterized in that: The mass ratio of the four raw materials of ruthenium salt, cobalt salt, melamine and ammonia water in the reaction system is 0-0.1:1.0-100.0:1.0-40.0:5.0-100.

0.

11. The use of the cobalt-based hexagonal nanosheets according to any one of claims 1 to 3, characterized in that: The cobalt-based hexagonal nanosheets are used for electrolyzing water to generate hydrogen.

Citation Information

Patent Citations

  • Preparation method for three-dimensional reticular nitrogen-doped graphene composite cobalt hydroxide hexagonal nano-sheet electrode material

    CN105118693A

  • Topology preparation method for ultrathin porous two-dimensional layered transition metallic oxide nanosheet array material

    CN107381658A

  • Monatomic metal doped alpha-cobalt hydroxide nanosheet as well as preparation method and application thereof

    CN114592213A